Emotion regulation in selective mutism: A comparison group study in children and adolescents with selective mutism. (July 2022) - Melfsen, Siebke; Jans, Thomas; Romanos, Marcel; Walitza, Susanne
Abstract: A deficit in emotion regulation skills could be an important factor influencing the vulnerability and maintenance of symptoms in selective mutism (SM). Unfortunately, to date only a few studies have examined emotion regulation in SM. Therefore, the present study investigated whether SM is associated with dysfunctional emotion regulation strategies. We compared a sample of 28 children and adolescents with SM (M = 12.66 years, SD = 3.98; 18 females) to 33 controls without SM (M = 12.45 years, SD = 3.18; 21 females). Both groups were investigated for the assessment of SM, social anxiety and emotion regulation using self and parent report questionnaires. We assumed that the disorder is associated with less adaptive and more maladaptive strategies, especially maladaptive cognitive strategies. Instead of significant differences in these overall values, only significant differences in individual emotion regulation strategies were found. In terms of adaptive strategies, children and adolescents with SM reported less problem-oriented behaviour and less cognitive problem-solving. Instead, they reported the maladaptive strategy of abandonment more often than the control group. In contrast to other anxiety disorders, children and adolescents with SM did neither report maladaptive cognitive strategies nor seek support more frequently than the control group. Their emotion regulation strategies are qualitatively closely related to the symptoms of SM, which makes it difficult to determine their independent significance. Trial registration: This study is registered with the ClinicalTrials.gov number NCT04233905.